Incentive-based demand response considering hierarchical electricity market: A Stackelberg game approach. (1st October 2017) - Yu, Mengmeng; Hong, Seung Ho
Highlights: Propose a resource trading framework for system-level dispatch of DR resources. Establish a two-loop Stackelberg game to capture the interactions between various actors. A unique Stackelberg equilibrium (SE) exists which provides optimal system solutions. Propose a distributed algorithm for seeking the SE without violating the privacy principle. Abstract: This paper proposes a novel incentive-based demand response model from the view of a grid operator to enable system-level dispatch of demand response resources. The model spans three hierarchical levels of a grid operator, multiple service providers, and corresponding customers. The grid operator first posts an incentive to service providers, who will then invoke sub-programs with enrolled customers to negotiate quantities of demand reduction via providing service provider incentives. In view of this hierarchical decision-making structure, a two-loop Stackelberg game is proposed to capture interactions between different actors. The existence of a unique Stackelberg equilibrium that provides optimal system solutions is demonstrated. Simulation results show that the proposed approach is effective in helping compensate system resource deficiency at minimum cost.